THU0510 Igg ACPA Level Increase Drives Rheumatoid Factor Response Maturation in Patients before Onset of Clinically Apparent Rheumatoid Arthritis - Falkenburg, W.; Bos, W.H.; Sohrabian, A.; Rönnelid, J.; Wolbink, G.; van Schaardenburg, D. (Annals of the rheumatic diseases, 2014)
Background In Rheumatoid Arthritis (RA) the pathophysiological role of both rheumatoid factor (RF) and anti citrullinated protein antibodies (ACPA) is still subject of debate. Since the antigen for RF is the constant domain (Fc) of IgG immunoglobulins in immune complexed form, we hypothesized that high or increasing titers of IgG ACPA targeting their antigen during the development of RA will provide an antigenic stimulus for RF producing B cells, leading to a rise in RF level and maturation of the RF response resulting in class-switching from IgM to IgG and IgA. Objectives To test this hypothesis we analyzed serial preclinical serum samples from a previously described cohort of patients during development of RA.[1] Methods Three sequential serum samples from 26 IgG ACPA positive RA patients who had donated blood before disease onset were selected and levels of IgG anti-cyclic citrullinated peptide 2 (anti-CCP2), IgM RF, IgG RF and IgA RF, measured using the Phadia ImmunoCap system[2], were plotted individually (Figure 1). Antibody level patterns were then grouped and frequencies of patterns definitely supporting, possibly supporting or refuting our hypothesis were determined. Results As shown in figure 1, 16 patients (62%) showed patterns directly supporting our hypothesis, including 11 patients with an IgG ACPA increase followed by or together with an IgM RF increase associated with an IgG/IgA RF increase, and 5 patients with high IgG ACPA levels at all three time points and high or rising IgM and IgG/IgA RF levels. Patterns compatible with, but not directly supporting the hypothesis were found in 8 patients (31%) including 3 patients without a significant IgG ACPA level increase and low RF levels at all time points, 2 patients with rising IgG ACPA only at the last time point together with minimal RF rise, and 3 patients with inconclusive patterns. 2 patients (8% of total) showed a pattern refuting our hypothesis, namely rising ACPA levels without rising RF or without evidence of class-switching. Conclusions Studying individual ACPA and RF profiles during the development of RA suggests that an IgG ACPA level increase drives rheumatoid factor response maturation in patients developing rheumatoid arthritis. References Nielen et al. Arthritis and Rheumatism 2004, Feb;50(2):380-6. Kokkonen et al. Arthritis Research & Therapy 2011, Feb 3;13(1):R13. Disclosure of Interest : None declared DOI 10.1136/annrheumdis-2014-eular.4582